Dampak Penolakan Produk Ekspor Indonesia terhadap Indikator Perekonomian dan Perdagangan - Ningsih, Rahayu; Epianingsih, Yuliana (Pusat Pengembangan Kompetensi Aparatur Perdagangan, 2025)
Indonesia is the world's fourth-largest exporter of instant noodles, following South Korea, China, and Thailand, with a positive growth trend of 9.47% over the past five years (BPS, 2024). However, despite this growth, in 2022, Indonesian instant noodle products were recalled in several export destination countries due to contamination with ethylene oxide (EtO) and 2-chloroethanol (2-CE). This issue has the potential to reduce market access and hinder Indonesia’s export performance in the future, not only for instant noodles but also for processed food products in general. In this case, the Recursive Dynamics Computable General Equilibrium (RDCGE) model was constructed to analyze the trade impact of the product recall on Indonesia's export performance. Under the assumption of a 9% export decline in the Malaysian market, the results indicate a GDP reduction of -0.003%, a total export volume decrease of -0.006%, and a trade balance decline of USD -0.0014 million. From a consumer protection perspective, if EtO and 2-CE contamination is not mitigated, it will not only affect market access abroad but also pose risks to consumer safety domestically, particularly concerning food safety issues. Long-term consumption of food contaminated with EtO and 2-CE can lead to serious health problems. Considering the recommendations from the analysis, Government has proposed that EtO and 2-CE be included in the priority list of residues to be harmonized within the Codex framework.